COMPARISON OF COMBINED ORAL & TOPICAL VERSUS TOPICAL CORTICOSTEROIDS AFTER FUNCTIONAL ENDOSCOPIC SINUS SURGERY OF NASAL POLYPOSIS - Hakim, Abdul; Khan, Muhammad Ahmed; Nawaz, Faiz Ul Hassan; Akram, Sumera (Pakistan Armed Forces Medical Journal, 2017)
Objective: To compare combined oral and topical corticosteroids versus only topical corticosteroids after functional endoscopic sinus surgery in cases of chronic rhinosinusitis with nasal polyposis.Study Design: Randomized controlled trials.Place and Duration of Study: The study was carried out at Combined Military Hospital (CMH) Quetta and Combined Military Hospital (CMH) Okara, from Apr 2014 to Apr 2016.Material and Methods: Total 150 cases of chronic rhino sinusitis with nasal polyps were selected. The cases were randomly divided into two groups. All the cases were operated via functional endoscopic sinus surgery. In group A, patients were given oral corticosteroids after the surgery (for one month duration, deltacortil 1mg/kg body weight for two weeks and tapering off in the next two weeks followed by local corticosteroid) and Group B individuals were put on topical corticosteroids soon after the surgery. All the cases were observed for any signs of recurrence. Recurrence of disease was defined as evidence of nasal polyposis on nasal endoscopy.Results: Mean age of patients was 39.22 ± 13.9 years and there were total 72 (48%) males and 78 (52%) females among all cases. There were 14 cases of recurrence of disease in group B while in group A, only 5 cases of recurrences were seen (p=0.047). It shows that group A patients had significantly less recurrence than cases of group B.Conclusion: Combination of oral and topical corticosteroids was significantly better with decrease recurrence as compared to topical steroids only in cases of chronic rhinosinusitis who were operated with functional endoscopic sinus surgery.